Failure of the large-N expansion in a bosonic tensor model - Aidan Herderschee; Michael Winer (Journal of High Energy Physics)
Abstract We study the tensor model generalization of the quantum p-spherical model in the large-N limit. While the tensor model has the same large-N expansion as the disordered quantum p-spherical model, its ground state is superextensive, in contradiction with large-N perturbation theory. Therefore, the large-N expansion of this model catastrophically fails at arbitrarily large-N, without any obvious signal in perturbation theory.